Once upon a time, there was you a novel - Berg, Elizabeth (New York : Random House, 2011)
Sharing nothing in common except their 16-year-old daughter, divorced parents John and Irene reconnect in the wake of a devastating tragedy and discover things about each other that they had not revealed during their marriage.
97311
Keywords: Divorced people; Teenage girls; Parent and child; Domestic fiction